Pentecostalism in Africa : experiences from Ghana's charismatic ministries - Asamoah-Gyadu, J. Kwabena (Johnson Kwabena) (Regnum mini book series., 2020)
Pentecostalism is the fastest growing stream of Christianity in the world. The real evidence for the significance of Pentecostalism lies in the actual churches they have built and the numbers they attract. In Africa, Pentecostalism has virtually become the representative face of Christianity with even historic mission denominations 'pentecostalising' their otherwise formal liturgical structures to survive. This work brings to a wider audience the insights and analysis from the author's book, Contemporary Pentecostal Christianity: Interpretations from an African Context. It interprets key theo